Foreign investment and the environment in international law / Jorge E. Viñuales. - Viñuales, Jorge E. (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2012)
Conflicts between foreign investment law and environmental law are becoming increasingly frequent. On the one hand, the rise of environmental regulation poses significant challenges to foreign investors in several industries. On the other, the surge in investment arbitration proceedings is making States aware of the important litigation risks that may result from the adoption of environmental regulation. This study of the relationship between these two areas of law adopts both a policy and a practical perspective. It identifies the major challenges facing States, foreign investors and their legal advisers as a result of the potential friction between investment law and environmental law and provides a detailed analysis of all the major legal issues on the basis of a comprehensive study of the jurisprudence from investment tribunals, human rights courts and bodies, the ICJ, the WTO, the ITLOS, the CJEU and other adjudication mechanisms.